1976
DOI: 10.1038/261558a0
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of an enzyme in platelet microsomes which generates thromboxane A2 from prostaglandin endoperoxides

Abstract: The microsomal fraction of horse and human platelets contains an enzyme which converts prostaglandin cyclic endoperoxides (PGG2 or PGH2) to a substance which is much more potent in contracting strips of rabbit aorta. This substance has the same characteristics as thromboxane A2, and can be distinguished from other products of arachidonic acid metabolism by differential bioassay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
193
0
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(197 citation statements)
references
References 18 publications
3
193
0
1
Order By: Relevance
“…The main source of TxA2 in the circulation is platelets (Needleman et al, 1976). Knauer et al (1981) and Gresele et al (1982) have shown that platelet activation is involved in allergic airway reactions.…”
Section: Plasma Txb2mentioning
confidence: 99%
“…The main source of TxA2 in the circulation is platelets (Needleman et al, 1976). Knauer et al (1981) and Gresele et al (1982) have shown that platelet activation is involved in allergic airway reactions.…”
Section: Plasma Txb2mentioning
confidence: 99%
“…The platelet provides a valuable cellular model for studying such prostaglandin receptors. The prostaglandin endoperoxides G2 and H2 are potent platelet stimulants (Hamberg et al, 1974;Willis et al, 1974), as is their major metabolic product, thromboxane A2 (Hamberg et al, 1975;Needleman et al, 1976). The study of these compounds is complicated by their lability in aqueous media, but analysis of their actions has been facilitated by the recent synthesis of stable analogues of prostaglandin H2 (Corey et al, 1975;Bundy, t Present address:…”
mentioning
confidence: 99%
“…Thromboxane A 2 (TXA 2 ) is generated from arachidonic acid by consecutive actions of cyclooxygenase (COX), existing as two isoforms of COX-1 and COX-2, and thromboxane synthase (TXAS) [1]. TXA 2 exhibits potent and diverse bioactivities, such as platelet…”
Section: Introductionmentioning
confidence: 99%